The Effectiveness of Assemblr Edu-Based Augmented Reality and Audio Media in Enhancing Science Concepts Understanding: A Quasi Experimental Design - Safrizal, Safrizal; Arafah, Kavita; Selpia, Reva; Hakimi, Musawer (Journal of Natural Science and Integration, 2026)
Conventional science instruction often relies on audio-based media, which often fails to help elementary students visualize complex, abstract scientific concepts, leading to suboptimal conceptual understanding. This study aimed to examine the effectiveness of Augmented Reality (AR) media in enhancing elementary students' conceptual understanding of science compared to audio-based media. A quasi-experimental design with a non-equivalent control group was employed, involving 50 fifth-grade students who were evenly assigned to experimental and control classes. Data were collected through pretests and posttests and analyzed using N-gain scores, effect size calculations, normality and homogeneity tests, and t-tests. The results showed that the experimental class achieved a mean pretest score of 41.6 and a posttest score of 67.2, while the control class achieved mean pretest and posttest scores of 42.6 and 49, respectively. The N-gain analysis showed greater improvement in the experimental class (0.44, moderate category) than in the control class. The effect size of 1.49 demonstrated a strong influence of AR-based media on students' learning outcomes. Furthermore, the t-test results confirmed significant differences both within groups (pretest–posttest) and between groups (posttest), emphasizing the superiority of AR media in science learning. It can therefore be concluded that Assemblr Edu-based AR media significantly improve elementary students' conceptual understanding of science. Keywords: augmented reality, students’ science concepts, science learning, audio media learning